2017
DOI: 10.1016/j.ijporl.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the inner ear structures in cystic fibrosis patients

Abstract: Objective Although prolonged use of antibiotics is very common in cystic fibrosis (CF) patients, no studies have assessed the changes in both cochlear and peripheral vestibular systems in this population. Methods We used human temporal bones to analyze the density of vestibular dark, transitional, and hair cells in specimens from CF patients who were exposed to several types of antibiotics, as compared with specimens from an age-matched control group with no history of ear disease or antibiotic use. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Although we did not observe significant synapse degradation/loss, we did observe changes in ABR wave III/I ratios indicating physiological changes between the peripheral and central auditory system (Dehmel et al, 2012;Gu et al, 2012;Lowe and Walton, 2015), which may be explained by "synaptopathy/hidden hearing loss, " or damage to the peripheral afferent system in the absence of significant hair cell loss (Schaette and McAlpine, 2011;Kujawa and Liberman, 2015). Growing evidence suggests that SGNs or their synapses are preferentially targeted by AGs (Liu et al, 2013;Hong et al, 2018) which has also been shown to be true in histological analysis from human cadavers (Sone et al, 1998;Pauna et al, 2017). Importantly, mechanistic understandings of the peripheral and central issues related to AG treatment should be elucidated further.…”
Section: Clinical Relevance and Future Studiessupporting
confidence: 58%
See 1 more Smart Citation
“…Although we did not observe significant synapse degradation/loss, we did observe changes in ABR wave III/I ratios indicating physiological changes between the peripheral and central auditory system (Dehmel et al, 2012;Gu et al, 2012;Lowe and Walton, 2015), which may be explained by "synaptopathy/hidden hearing loss, " or damage to the peripheral afferent system in the absence of significant hair cell loss (Schaette and McAlpine, 2011;Kujawa and Liberman, 2015). Growing evidence suggests that SGNs or their synapses are preferentially targeted by AGs (Liu et al, 2013;Hong et al, 2018) which has also been shown to be true in histological analysis from human cadavers (Sone et al, 1998;Pauna et al, 2017). Importantly, mechanistic understandings of the peripheral and central issues related to AG treatment should be elucidated further.…”
Section: Clinical Relevance and Future Studiessupporting
confidence: 58%
“…Animal models have demonstrated varying degrees of AG-induced cochlear hair cell damage and subsequent hearing loss ( Huth et al, 2011 ; Ogier et al, 2020 ). However, emerging evidence suggests that SGNs, and their specialized ribbon synapses may also be damaged by AGs ( Sone et al, 1998 ; Pauna et al, 2017 ; Hong et al, 2018 ). Such peripheral pathology evidenced in models of noise-induced and age-related hearing loss ( Kujawa and Liberman, 2015 ), has been shown to contribute to central maladaptive plasticity ( Gold and Bajo, 2014 ; Eggermont, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… 5 Further research is needed to define the possible characteristics that underlie this toxicity. Pauna et al 8 found histopathological changes due to exposure to aminoglycosides in the vestibular structures of human temporal bone specimens from deceased donors with CF. However, one can speculate that the vestibular structures are intrinsically changed in patients with CF.…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesis of a functional interplay between CFTR and pendrin in the stria vascularis is tempting and would require the precise identification of the cell types expressing CFTR. Various degrees of hearing loss and alteration of the inner ear structures, including atrophy of the stria vascularis, have been described in CF patients [118]. Although these derangements have been linked to the use of ototoxic antibiotics, it has been suggested that exposure to aminoglycosides is not the only causal factor for hearing loss in CF [119].…”
Section: The Inner Earmentioning
confidence: 99%